Myroides indicus sp nov., isolated from garden soil - Ram, Hari; Kumar, Alok; Thomas, Lebin; Dastager, Syed Gulam; Mawlankar, Rahul R.; Singh, Ved Pal (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel aerobic, non-motile, rod-shaped, catalase-and oxidase-positive bacterial strain, designated UKS3(T), was isolated from garden soil, and subjected to polyphasic taxonomic analysis. Strain UKS3(T) formed whitish, viscous colonies on nutrient agar and was Gram-staining negative. Phylogenetic analysis, based on 16S rRNA gene sequence, showed that maximum pairwise similarity occurs with representatives of the genus Myroides. The most closely related species include Myroides marinus JS-08(T) (92.7 % sequence similarity), Myroides phaeus MY15(T) (92.7 %), Myroides odoratus DSM 2801(T) (91.5 %) and Myroides odoratimimus CCUG 39352(T) (91.4 %). Strain UKS3(T) contained menaquinone-6 (MK-6) as the major respiratory quinone and iso-C-15 : 0 (40.2 %), anteiso-C-15 : 0 (9.4 %) and iso-C-17 : 0 3-OH (8.5 %) as major fatty acids. Phosphatidylethanolamine, phospholipids and three aminolipids were the major polar lipids. The DNA G + C content of strain UKS3(T) was 36.8 +/- 2.0 mol%. On the basis of phenotypic, chemotaxonomic and molecular analysis, strain UKS3(T) represents a novel species of the genus Myroides, for which the name Myroides indicus sp. nov., is proposed. The type strain is UKS3(T) (= DSM 28213(T) = NCIM 5555(T)).

Multipurpose cellulases of Promicromonospora sp. VP111, with broad substrate specificity and tolerance properties - Thomas, Lebin; Ram, Hari; Singh, Ved P. (Journal of Basic Microbiology, 2023)
Cellulolytic actinobacterium, Promicromonospora sp. VP111 concomitantly produced cellulases (CELs), xylanase and pectinase when grown on commercial cellulose and untreated agricultural lignocellulosic residues (wheat straw and sugarcane bagasse). Secreted CELs hydrolyzed (enhanced with Co2+ ion) multiple cellulosic substrates, including sodium carboxymethyl cellulose (Na-CMC), Whatman filter paper no. 1, microcrystalline cellulose (avicel), p-nitrophenyl-beta-D-glucopyranoside (pNPG), laminarin, and cellulose powder. The CELs showed stabilities in the presence of various chemicals, including glucose (0.2 M), detergents (1%, w/v or v/v), denaturants (1%, w/v or v/v), and sodium chloride (NaCl, 30%, w/v). The CELs were fractionated using ammonium sulfate precipitation and dialysis. Activities (%) of fractionated CELs were retained at 60 degrees C for endoglucanase/carboxymethyl cellulase (CMCase) (88.38), filter paper cellulase (FPase) (77.55), and beta-glucosidase (90.52), which indicated of thermo-stability. Similarly, the activities (%) for CMCase (85.79), FPase (82.48), and beta-glucosidase (85.92) at pH 8.5 indicated of alkaline-stability. Kinetic factors, K-m and V-max for endoglucanase component of fractionated CELs were 0.014 g/l and 158.23 mu M glucose/min/mL, respectively. Fractionated CELs yielded activation energies (kJ/mol) of 17.933, 6.294, and 4.207 for CMCase, FPase, and beta-glucosidase activities, respectively in linear thermostable Arrhenius plots. Thus, this study reports on the multipurpose CELs from an untreated agricultural residue utilizing Promicromonospora in relation to broad substrate specificity, halo-tolerance, alkaline-tolerance, detergent-tolerance, thermo-tolerance, organic solvent-tolerance, and end product-tolerance.
Keywords: cellulases; cellulose; Endoglucanase; Lignocellulose; Promicromonospora sp; VP111